P-43 Evaluation of opiate prescribing and adjustment in renal impairment in an acute medical admissions unit. (1st March 2017) - Howorth, Kate; Frew, Katie; Atkinson, Jane; Grogan, Eleanor; Green, Alastair; Foggett, Emma
Abstract : Background: Incorrect opioid prescribing can have significant consequences for patient safety and quality of care (1), adjustment of opioid is often needed in renal impairment (2, 3). The audit aimed to assess if an acute medical assessment unit (AMU) was meeting current guidance regarding opioid prescribing in acute medical admissions Methodology: A retrospective case note audit was conducted of all patients admitted to AMU who were prescribed an opioid from 1 st to 7 th March 2016. Notes were reviewed to establish: the opioid and dose prescribed; any change to an established opioid or dose on admission; initiation dose of opioid if opioid naïve; any documentation of a rationale behind prescribing in impaired renal function. Laboratory results were reviewed to look for AKI and calculate eGFR. The audit standards used were the local trust guidelines (4) and the North of England Cancer Network Palliative Care Guidelines (5). Results: 14 patients were prescribed an opioid and only 5 met the audit standards. 4 out of 6 opioid naive patients commenced on morphine IR solution were prescribed a dose higher than recommended. 1 of 5 patients on a long-acting opioid had a correct PRN dose prescribed. A half of patients with a reduced eGFR were prescribed morphine. There was no documentation regarding rationale behind opioid prescribing. Conclusion: The results demonstrated that opioid prescribing on AMU did not adhere to local or regional guidance. Recommendations: 1. Conduct a live audit of patients admitted to AMU over two weeks to expand data 2. Develop specific guidance for opioid adjustment in AKI and for initiating opioids in patients with a reduced eGFR on AMU. 3. Share audit findings and conduct teaching for acute medicine trainees regarding opioid prescribing in acute medical admissions. 4. Repeat audit after interventions taken place.